Fluoxetine Affects Glycolytic Pathway of C6 Rat Glioma Cells - Hisab, Ahmed S. (European Scientific Journal, ESJ, 2018)
Antidepressants (ADs) such as fluoxetine is known to target and inhibit the electron transport chain of mitochondrial, effects on rat C6 glioma cell function are expected. Also, it has been shown that fluoxetine can inhibit mitochondrial respiration in pancreatic beta cells; however whether this drug can also directly affect glycolytic metabolism is unknown. To address this idea, I have investigated effect of fluoxetine on the bioenergetics of C6 glioma. MTS assay was conducted as an indicator of the metabolic activity of C6 cell lines. Oxidative respiration was measured via oxygen consumption rate (OCR), anaerobic glycolysis was determined with lactate electrodes, where mitochondrial redox state was monitored via NAD (P) H autofluorescence. The metabolic assays showed glucose stimulated MTS reduction cells in a time and concentration dependent manner whereas, the other three mitochondrial fuels did not stimulated it in C6 glioma cells. Methylpyruvate substrate stimulated OCR, neither both glucose and Î±-ketoisocaproate. Glucose inhibited OCR and increased lactate production compared to the control. Glucose failed to affect NADPH levels. Fluoxetine inhibited OCR at 10 mM glucose. However, it did not affect OCR at 10 mM Î±-ketoisocaproate. The above results showed that C6 glioma cells are mainly depending on the glycolytic pathway and that was inhibited by Fluoxetine. In conclusion, since fluoxetine was inactive in the presence of Î±-ketoisocaproate our data suggest that the point of major action for these ADs in C6 glioma cells is glycolysis.